A gold-based nanoscale enzyme, and a preparation method and kit thereof
Patent Information
- Application Number
- CN202611087491.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-22
AI Technical Summary
然而,现有中熵或高熵纳米酶体系,如PdPtRhCu、PdRhRuCu等,虽然在催化性能方面有所优化;但是,其在免疫检测应用中仍存在明显不足:一方面,难以实现抗体的稳定固定;另一方面,抗体偶联效率较低且稳定性较差,在复杂体系或储存过程中易发生脱附,从而导致检测信号衰减;此外,现有纳米酶难以同时兼顾高催化活性与高效生物偶联能力,限制了其在免疫层析检测中的应用
[0056] The gold-based nanozyme of this application introduces Au into a multi-metal system, constructing an Au-S functional interface on the nanozyme surface that specifically binds to the thiol groups in antibody proteins. This, combined with the synergistic effect of the multi-metal system and the high specific surface area and multi-site characteristics brought by the mesoporous structure, achieves efficient and stable antibody conjugation. While maintaining excellent peroxidase-like catalytic activity, the gold-based nanozyme of this application improves antibody conjugation efficiency and probe stability, thereby enhancing the signal output capability in immunochromatographic test strips. Immunochromatographic test strips constructed based on the gold-based nanozyme of this application can achieve rapid detection, and signal amplification through enzymatic reactions improves detection sensitivity. Compared with traditional gold nanoparticles and non-gold-based nanozymes, the gold-based nanozyme of this application has advantages in antibody immobilization efficiency, signal amplification capability, and detection performance.
Smart Images

Figure CN122591944B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of nanozyme technology, and in particular to a gold-based nanozyme and its preparation method and kit. Background Technology
[0002] Multimetallic alloy nanomaterials have attracted widespread attention in energy catalysis, biosensing, and biodetection due to their tunable electronic structure, diverse surface active sites, and excellent catalytic performance. In recent years, medium-entropy and high-entropy nanomaterials have demonstrated significant advantages in regulating surface electronic states, lowering reaction energy barriers, and improving catalytic stability through multimetallic synergistic effects. This has enabled them to exhibit excellent catalytic performance in nanozyme systems such as peroxidase-like enzymes, and they show promising application prospects in immunoassay and food safety detection. However, existing medium-entropy or high-entropy nanozyme systems, such as PdPtRhCu and PdRhRuCu, while showing improvements in catalytic performance, still have significant limitations in immunoassay applications: firstly, stable antibody immobilization is difficult to achieve; secondly, antibody conjugation efficiency is low and stability is poor, easily desorbing in complex systems or during storage, leading to signal attenuation; furthermore, existing nanozymes cannot simultaneously achieve high catalytic activity and efficient bioconjugation capabilities, limiting their application in immunochromatographic detection. Summary of the Invention
[0003] The purpose of this application is to provide an improved gold-based nanozyme, its preparation method, and a kit.
[0004] To achieve the above objectives, this application adopts the following technical solution:
[0005] This application discloses a gold-based nanozyme containing Au, Pt, Rh and Cu elements. The gold-based nanozyme has a multi-metal synergistic structure and a mesoporous structure, and the Au element is at least partially exposed on the surface of the gold-based nanozyme.
[0006] Among them, the multi-metal synergistic structure refers to the multi-principal nanostructure formed by Au, Pt, Rh and Cu multi-metals with uniform elemental distribution at the atomic and / or nanoscale. This multi-principal nanostructure utilizes the electronic and geometric effects between different metals to generate a synergistic effect of "1+1>2", and regulates the electronic structure and active site distribution on the material surface through the medium entropy effect.
[0007] It should be noted that the gold-based nanozyme of this application, by introducing Au element into the multi-metal entropy nanozyme system, constructs a functional interface with Au-S specific coordination ability on the surface of the gold-based nanozyme, achieving efficient and stable antibody immobilization. Simultaneously, the mesoporous structure provides a high specific surface area and multi-site binding interface, improving antibody loading capacity. The synergistic effect of Au, Pt, Rh, and Cu further optimizes the surface electronic structure, endowing the material with excellent peroxidase-like catalytic activity, enabling it to possess signal amplification capabilities. Therefore, the gold-based nanozyme of this application achieves integrated biorecognition and signal amplification, significantly improving detection sensitivity and stability, overcoming the shortcomings of insufficient catalytic performance of traditional gold nanoparticles and limited coupling ability of non-gold-based nanozymes.
[0008] In some implementations, the molar ratios of Au, Pt, Rh, and Cu in the gold-based nanozyme are (0.5-3):(1-3):(0.5-2):(0.5-2).
[0009] In some implementations, the molar ratio of Au, Pt, Rh, and Cu in the gold-based nanozyme is preferably 1:2:1:1 in sequence.
[0010] It should be noted that the gold-based nanozyme of this application can optimize its catalytic performance and interfacial function by adjusting the ratio of Au to Pt, thereby regulating the electronic structure and active site distribution on the nanozyme surface.
[0011] In some implementations, gold-based nanozymes have a dendritic structure.
[0012] This application also discloses a method for preparing the gold-based nanozyme of this application, including the following steps:
[0013] (1) Adding a surfactant to a solvent to form a uniform dispersion system, wherein the surfactant is able to form a micelle confinement structure in the solvent; for example, in an aqueous solvent, the surfactant can be an amphiphilic surfactant, such as a block copolymer having both hydrophilic and hydrophobic segments.
[0014] (2) Add an acidic solution to the homogeneous dispersion system to adjust the reaction environment to a strongly acidic environment;
[0015] (3) Add metal precursor solutions of Au, Pt, Rh and Cu in sequence;
[0016] (4) Add a mild reducing agent and react at 70-90℃ for 8-24 h;
[0017] (5) Centrifuge, wash and dry to obtain the gold-based nanozyme of this application.
[0018] It should be noted that the gold-based nanozyme preparation method of this application adopts a surfactant-assisted one-pot wet chemical reduction strategy, which realizes the synergistic reduction and assembly of multi-metal precursors under the action of a reducing agent to form nanoparticles with uniform elemental distribution and mesoporous structure, namely the gold-based nanozyme of this application; the preparation method of this application is simple and easy to operate, and is suitable for the large-scale production of gold-based nanozymes.
[0019] It should also be noted that the preparation method of this application utilizes a strongly acidic environment, for example, using HCl to adjust the pH to 0.5-1.5, to reduce the difference in reduction rates and achieve simultaneous co-reduction of multiple metal ions. Combined with surfactants, such as block copolymers PF127 or PEO-b-PMMA, a micellar confinement structure is formed, allowing metal ions to be uniformly dispersed at the nanoscale. Simultaneously, a mild reducing agent, such as L-ascorbic acid, is used to avoid explosive nucleation, and a long reaction at 70-90℃ promotes atomic diffusion and rearrangement, ultimately forming a homogeneous multi-metal solid solution structure. Furthermore, the high entropy effect further reduces the system's free energy, thermodynamically inhibiting metal phase separation, thereby obtaining a structurally stable AuPtRhCu medium-entropy nanozyme. This application inhibits the preferential growth behavior of Au through a strongly acidic, weakly reducing system, enabling Au to be simultaneously co-reduced with Pt, Rh, and Cu into the initial crystal nucleus, and achieving atomic-level uniform solid solution during subsequent heat treatment, thus avoiding Au phase separation or enrichment. Meanwhile, Au exists in the alloy in a partially exposed form, forming stable Au-S specific binding sites, enabling efficient coupling and stable immobilization of biomolecules such as antibodies; at the same time, after Au enters the Pt-based lattice, it regulates its electronic structure and forms a multi-metallic electronic synergistic effect with Rh and Cu, optimizing the adsorption and reaction pathways of catalytic intermediates, thereby achieving synergistic enhancement of biological interface function and catalytic performance.
[0020] In this application, a mild reduction method is employed, primarily referring to the use of a mild reducing agent with moderate reducing power. During the reaction, the metal ions undergo gradual reduction at a low electron release rate, thus avoiding the instantaneous explosive nucleation caused by strong reducing agents. Mild reduction is mainly controlled by the type of reducing agent, preferably using mild reducing agents such as ascorbic acid-based reducing agents, polyol-based reducing agents, sugar-based reducing agents, and organic acid-based reducing agents, rather than strong reducing agents such as sodium borohydride and hydrazine hydrate. The mild reducing agent used in this application is characterized by the fact that, under acidic conditions, the metal precursor will not be completely reduced in a short time, but will gradually complete the reduction, nucleation, and growth processes over a certain period, making the reduction process of each metal ion more coordinated and conducive to the formation of polymetallic nanomaterials with uniform composition and stable structure. Experimentally, during mild reduction, the color of the reaction solution typically changes from the yellowish-brown (or yellow) of the precursor to black, rather than turning black immediately after the addition of the reducing agent. This color change reflects the gradual formation process of the metal nanoparticles and can serve as a direct experimental phenomenon for judging whether the reaction is a mild reduction. Conversely, when strong reducing agents such as sodium borohydride are used, the metal ions in the system will be rapidly reduced in a very short time, and the solution color will quickly change from yellow to black, forming a burst of nucleation. This can easily lead to uneven particle size distribution, elemental segregation, and rapid dendritic growth, which is not conducive to the controllable preparation of the multi-metal entropy nanozyme of this application.
[0021] In some implementations, the surfactant is a block copolymer.
[0022] In some implementations, the block copolymer is a diblock copolymer or a triblock copolymer.
[0023] In some implementations, the surfactant is selected from at least one of PEO-b-PMMA block copolymer, polystyrene-b-polyethylene oxide (PS-b-PEO), Pluronic F127, polyvinylpyrrolidone block copolymer, and polyethylene glycol block copolymer.
[0024] In some implementations, the solvent is water or a mixture of water and an organic solvent.
[0025] In some implementations, the concentration of the surfactant in the solvent is 1.25-10 mg / mL.
[0026] In some implementations, step (1) involves ultrasonically dispersing the surfactant to form a uniform dispersion system.
[0027] In some implementations, the acidic solution used in step (2) is a hydrochloric acid solution.
[0028] In some implementations, the concentration of the hydrochloric acid solution is 4-8 mol / L.
[0029] In some implementations, the pH of the strongly acidic environment is 0.5-1.5.
[0030] It should be noted that the purpose of adding acidic solution to adjust pH in this application is not simply to acidify the system, but to regulate the nucleation and crystal growth process by reducing the reduction kinetics of metal ions. Lower pH, such as 0.5-1.5, can significantly slow down the reduction rates of Au, Pt, Rh, and Cu precursors, allowing for continuous and slow deposition of metal atoms. This provides sufficient time for surfactant micelle adsorption and template-directed growth, resulting in high-entropy nanozymes with uniform size, ordered mesoporous structure, and uniform elemental distribution. Conversely, at higher pH conditions, metal ions undergo rapid reduction and instantaneous burst nucleation, leading to rapid anisotropic growth and ultimately forming dendritic, non-mesoporous structures, potentially causing multi-metal segregation. If the acidity is too high, for example below 0.5, it will make the metal chloride complex overly stable, severely inhibiting the reduction reaction and even affecting template stability and simultaneous multi-metal co-reduction. Therefore, there exists a suitable acidity window, such as 0.5-1.5, which is essentially about achieving the best balance between "reaction rate" and "structural regulation". pH 0.5-1.5 is the optimal condition for achieving this balance and obtaining high-quality AuPtRhCu mesoporous high-entropy nanozymes.
[0031] In some implementations, the Au metal precursor solution used in step (3) is at least one of chloroauric acid, sodium tetrachloroaurate, and potassium tetrachloroaurate.
[0032] In some implementations, the metal precursor solution of Pt is at least one of potassium chloroplatinate, chloroplatinic acid, sodium hexachloroplatinate, potassium hexachloroplatinate, and ammonium hexachloroplatinate.
[0033] In some implementations, the metal precursor solution of Rh is at least one of sodium rhodium chloride, rhodium chloride, potassium rhodium chloride, rhodium chloride, and hydrated rhodium chloride.
[0034] In some implementations, the metal precursor solution of Cu is at least one of copper chloride, copper nitrate, copper sulfate, and copper acetate.
[0035] In some implementations, the mild reducing agent used in step (4) is at least one of ascorbic acid reducing agents, polyol reducing agents, sugar reducing agents, and organic acid reducing agents.
[0036] In some implementations, the mild reducing agent is at least one selected from L-ascorbic acid, sodium ascorbate, ethylene glycol, glycerol, glucose, fructose, maltose, and sodium citrate. In some implementations, L-ascorbic acid is preferred.
[0037] This application also discloses the application of the gold-based nanozyme of this application in the preparation of protein-coupled reagents, nanozyme immunoprobes, or immunochromatographic test strips.
[0038] This application also discloses a protein coupling method, comprising the following steps:
[0039] (1) Disperse the gold-based nanozyme of this application in an aqueous solution;
[0040] (2) Adjust the pH of the system to 7.5-9.0;
[0041] (3) Add antibody and incubate to fix the antibody on the surface of gold-based nanozyme through Au-S coordination;
[0042] (4) Add a blocking agent to reduce non-specific adsorption;
[0043] (5) Centrifuge and resuspend to obtain nanozyme immunoprobes for protein coupling.
[0044] It should be noted that the protein conjugation method of this application, due to the use of the gold-based nanozyme of this application, has higher antibody conjugation efficiency and probe stability, resulting in higher detection sensitivity and stability of protein conjugation detection.
[0045] It should also be noted that the protein conjugation method of this application uses a gold-based medium-entropy nanozyme as a carrier, and achieves efficient antibody immobilization through Au-S coordination under pH 7.5-9.0 conditions. Compared with traditional gold nanoparticle conjugation methods, this method has significant advantages: First, the Au active sites on the surface of the nanozyme are uniformly distributed and regulated by the multi-metal electronic structure, maintaining a stable surface charge state over a wide pH range, thereby significantly broadening the conjugation reaction window and improving process robustness; second, the mild one-step incubation method avoids complex chemical activation processes, reducing structural damage to the antibody during the reaction and maximizing its biological activity; in addition, the nanozyme has a dendritic mesoporous structure with a high specific surface area, which can significantly improve antibody loading capacity and binding efficiency; at the same time, the subsequent blocking step can effectively reduce non-specific adsorption and improve the signal-to-noise ratio; finally, this method has high structural stability and batch-to-batch consistency, ensuring that the obtained immunoprobes maintain good dispersibility and functional stability during centrifugation, resuspension, and long-term storage, thereby significantly improving the reliability and reproducibility of the immunoassay system.
[0046] In some implementations, the blocking agent is at least one of bovine serum albumin, casein, and polyethylene glycol.
[0047] This application also discloses a nanozyme immune probe, which is formed by conjugating the gold-based nanozyme of this application with an antibody.
[0048] It should be noted that the nanozyme immunoprobe of this application, due to the use of the gold-based nanozyme of this application to conjugate with the antibody, significantly improves the antibody conjugation efficiency and probe stability, thereby enhancing the signal output capability in the immunochromatographic test strip.
[0049] It should also be noted that the gold-based medium-entropy nanozyme used in this application exhibits significant structural and functional advantages compared to traditional AuNPs when used for protein conjugation. Firstly, this nanozyme possesses an AuPtRhCu multimetallic mesoporous structure, where Au exists in a highly dispersed form on the surface, providing a high density of electronically optimized Au-S binding sites. Simultaneously, the introduction of Pt, Rh, and Cu modulates the electronic structure of the Au surface, enhancing the stability of Au-S coordination and thus significantly improving antibody conjugation efficiency and binding strength. Secondly, this nanozyme possesses a mesoporous dendritic mesoporous structure, significantly increasing the specific surface area, providing more antibody loading sites, improving the biomolecular carrying capacity per unit particle, and enhancing the exposure of antibody spatial configuration, thereby improving immune recognition efficiency. Furthermore, the overall electronic stability brought by the medium-entropy structure effectively inhibits surface ligand exchange and antibody desorption, improving the structural stability of the probe during incubation and washing, and significantly enhancing its anti-interference ability in complex matrices. Meanwhile, the surface charge and interfacial properties of this nanozyme can be modulated through multi-metal synergistic effects, broadening the pH range applicable to the coupling reaction and enhancing process robustness and batch-to-batch consistency. More importantly, this nanozyme also possesses peroxidase-like catalytic activity, enabling signal amplification after antibody conjugation. This allows for the integrated construction of probes that combine biorecognition and catalytic signal amplification, significantly improving the sensitivity and practicality of immunoassay systems.
[0050] This application also discloses an immunochromatographic test strip, which includes a sample pad, a nitrocellulose membrane and an absorbent pad. The nitrocellulose membrane is provided with a test line and a control line, wherein the test line or control line contains the nanozyme immunoprobe of this application.
[0051] It should be noted that the immunochromatographic test strip of this application, due to the use of the nanozyme immunoprobe prepared by the gold-based nanozyme of this application, can not only achieve rapid detection, but also achieve signal amplification through enzymatic reaction, significantly improving detection sensitivity, and has obvious advantages in antibody fixation efficiency, signal amplification capability and detection performance.
[0052] It should also be noted that this application uses a gold-based medium-entropy nanozyme as an immunoassay probe. This test strip not only possesses the rapid detection capabilities of traditional colloidal gold test strips, but also achieves secondary signal amplification through the peroxidase-like catalytic activity of the nanozyme, thereby constructing a dual-modal detection system of "color signal + catalytically enhanced signal," significantly improving detection sensitivity and broadening the linear range. Simultaneously, the multi-metal (Au / Pt / Rh / Cu) synergistic structure endows the nanoprobe with higher and more stable catalytic activity, making the colorimetric reaction rate controllable and the signal output more stable, avoiding the problems of excessively rapid reactions or signal attenuation in traditional enzyme systems. Furthermore, the medium-entropy alloy structure and dendritic mesoporous morphology significantly reduce non-specific adsorption and improve anti-interference ability in complex matrix samples, enabling the test strip to maintain stable detection performance in actual samples such as serum, milk, and food extracts. At the same time, this nanozyme probe has excellent structural stability and dispersibility, ensuring good detection consistency and repeatability of the test strip during long-term storage and transportation, thus significantly improving the practicality and application potential of the immunochromatographic system.
[0053] This application also discloses the application of the gold-based nanozyme, the nanozyme immunoprobe, or the immunochromatographic test strip of this application in immunoassay.
[0054] This application also discloses a kit for immunoassay, which contains the gold-based nanozyme of this application, the nanozyme immunoprobe of this application, or the immunochromatographic test strip of this application.
[0055] Due to the adoption of the above technical solutions, the beneficial effects of this application are as follows:
[0056] The gold-based nanozyme of this application introduces Au into a multi-metal system, constructing an Au-S functional interface on the nanozyme surface that specifically binds to the thiol groups in antibody proteins. This, combined with the synergistic effect of the multi-metal system and the high specific surface area and multi-site characteristics brought by the mesoporous structure, achieves efficient and stable antibody conjugation. While maintaining excellent peroxidase-like catalytic activity, the gold-based nanozyme of this application improves antibody conjugation efficiency and probe stability, thereby enhancing the signal output capability in immunochromatographic test strips. Immunochromatographic test strips constructed based on the gold-based nanozyme of this application can achieve rapid detection, and signal amplification through enzymatic reactions improves detection sensitivity. Compared with traditional gold nanoparticles and non-gold-based nanozymes, the gold-based nanozyme of this application has advantages in antibody immobilization efficiency, signal amplification capability, and detection performance. Attached Figure Description
[0057] Figure 1 This is a schematic diagram of the preparation process of gold-based nanozymes according to an embodiment of this application;
[0058] Figure 2The images show a comparison of the catalytic performance and morphology of AuPtRhCu nanozymes prepared under different Au / Pt ratios in the embodiments of this application. Among them, Figure a shows the catalytic kinetic curves of nanozymes with different Au / Pt ratios within 6 min, Figure b shows the comparison of the catalytic activity intensity of nanozymes with different Au / Pt ratios, and Figures c to f are the TEM images corresponding to different Au / Pt ratios, namely 2:1:1:1, 1:1:1:1, 1:2:1:1, and 1:3:1:1, respectively.
[0059] Figure 3 The image shows the structure of the gold-based nanozyme prepared under the optimized ratio conditions of Au:Pt:Rh:Cu = 1:2:1:1 in the embodiments of this application; wherein, a is a scanning electron microscope (SEM) image, b is a transmission electron microscope (TEM) image, c is an energy dispersive spectroscopy (EDS) image, d is an elemental distribution map, and e is a dynamic light scattering (DLS) test result.
[0060] Figure 4 Figure 1 shows the results of the AuPtRhCu nanozyme peroxidase activity evaluation in the embodiments of this application; wherein, figure a is a comparison of catalytic color development of different materials, figure b is a comparison of specific activity of different materials, figure c is the enzyme kinetic curve of AuPtRhCu nanozyme, and figure d is the Lineweaver-Burk double reciprocal fitting curve.
[0061] Figure 5 The figures show the comparison results of the conjugation efficiency of different nanoparticles with antibodies in the embodiments of this application; where, figure a is AuPtRhCu nanozyme, figure b is PdPtRhCu nanozyme, and figure c is AuNPs;
[0062] Figure 6 This is a schematic diagram illustrating the binding modes of different nanomaterials to antibody proteins in the embodiments of this application;
[0063] Figure 7 This is a schematic diagram of the structure of the immunochromatographic test strip in the embodiments of this application;
[0064] Figure 8 This is a schematic diagram illustrating the immunochromatographic detection principle based on AuPtRhCu nanozyme immunoprobe in the embodiments of this application. Detailed Implementation
[0065] Existing medium- or high-entropy nanozyme systems mainly focus on optimizing catalytic performance, with insufficient attention paid to surface chemical properties and biological interface functions. This results in significant shortcomings in their application in immunoassay. For example, non-gold-based nanozymes lack specific bioconjugation interfaces on their surfaces. They mainly bind to proteins through electrostatic interactions, hydrophobic interactions, or weak coordination interactions, which are non-specific physical adsorptions. This makes it difficult to achieve stable antibody immobilization, resulting in low antibody conjugation efficiency and poor stability. They are also prone to desorption in complex systems or during storage, leading to attenuation of the detection signal.
[0066] In the field of bioconjugation, Au-S bonds are widely used for the immobilization of proteins and nucleic acids due to their stable binding, mild reaction conditions, and ease of operation. Therefore, introducing Au into nanozyme systems and constructing functional interfaces with Au-S bond binding capabilities on their surfaces is an effective strategy for achieving efficient bioconjugation. However, introducing Au into multi-metal systems still faces certain challenges: the standard redox potentials and reaction kinetics of different metal ions vary significantly, and their co-reduction process is affected by factors such as coordination environment, surface energy, and reducing agents, leading to complex nucleation and growth processes. This makes it difficult to obtain multi-metal nanomaterials with uniform composition and stable structure, and also easily results in metal phase separation, thus affecting material properties.
[0067] Therefore, the key technical challenge in introducing Au into multimetal nanozyme systems is to achieve the controllable introduction of Au elements and construct nanostructures that combine the specific binding interface of Au-S with the synergistic catalytic properties of multimetals, thereby realizing the synergistic optimization of bioconjugation ability and catalytic performance.
[0068] This application creatively employs a surfactant-assisted one-pot wet chemical reduction strategy to achieve the synergistic reduction and assembly of multi-metal precursors under the action of a reducing agent, forming nanoparticles with uniform elemental distribution and mesoporous structure, thereby obtaining the mesoporous AuPtRhCu gold-based nanozyme of this application, which contains Au, Pt, Rh and Cu elements. The gold-based nanozyme has a multi-metal synergistic structure and a mesoporous structure, and the Au element is at least partially exposed on the surface of the gold-based nanozyme.
[0069] In some embodiments, the surfactant-assisted one-pot wet chemical reduction strategy of this application includes the following steps:
[0070] (1) Dissolve the surfactant in a solvent and sonicate it at room temperature to form a uniform dispersion system;
[0071] (2) Add an acidic solution to the system to adjust the reaction environment so that the surfactant can form a stable self-assembled structure, and at the same time regulate the coordination state and dispersion behavior of the multi-metal precursor;
[0072] (3) Add metal precursor solutions of Au, Pt, Rh and Cu to the system to make them uniformly dispersed;
[0073] (4) Add a reducing agent to induce a synergistic reduction reaction of the metal ions under mild conditions, and nucleate and grow under heating conditions to form a multi-principal nanostructure with uniform element distribution;
[0074] (5) After the reaction is completed, gold-based nanozymes are obtained by centrifugation and washing.
[0075] The nanozymes prepared by the above method have a dendritic mesoporous structure and a uniform distribution of multiple metals.
[0076] In the above preparation process: the surfactant is selected from at least one of PEO-b-PMMA block copolymer, Pluronic F127, polyvinylpyrrolidone, and polyethylene glycol; preferably, the surfactant is a block copolymer or triblock copolymer, such as Pluronic F127 or PEO-b-PMMA; the solvent is water or a mixture of organic solvent and water, preferably deionized water; the acidic solution is 6.0 M hydrochloric acid, with an added volume of 0.2-0.5 mL, preferably 0.4 mL; the reducing agent is an L-ascorbic acid aqueous solution, with an added amount of 2-5 mL, preferably 4 mL; the reaction temperature is 70-90℃, preferably 80℃; and the reaction time is 8-24 h, preferably 12 h.
[0077] The molar ratio of Au, Pt, Rh, and Cu is (0.5-3):(1-3):(0.5-2):(0.5-2), preferably 1:2:1:1. By adjusting the ratio of Au to Pt, the electronic structure and active site distribution on the surface of the nanozyme can be regulated, thereby optimizing its catalytic performance and interfacial function.
[0078] In some embodiments, this application further provides a method for evaluating the activity of nanozyme-type peroxidases, comprising:
[0079] (1) The nanozyme was added to the TMB and H2O2 system, and its catalytic color development ability was evaluated by measuring the change in absorbance at 652 nm;
[0080] (2) The specific activity of nanozymes per unit mass was calculated by monitoring the rate of change of absorbance in the initial stage of the reaction;
[0081] (3) By changing the substrate concentration, Michaelis-Menten kinetic curves were established, and Km and Vmax were calculated to evaluate the substrate affinity and catalytic efficiency of the nanozyme.
[0082] In some embodiments, this application also provides a protein coupling method based on gold-based nanozymes, comprising the following steps:
[0083] (1) Dilute the nanozyme dispersion and adjust it to a weakly alkaline condition so that the pH of the system is 7.5-9.0, preferably pH 8.2;
[0084] (2) Add antibody protein to the system and incubate at room temperature to allow the antibody to bind to the surface of the nanozyme;
[0085] (3) Add a blocking agent to block the unbound sites on the surface of the nanozyme, and remove the unbound antibodies by centrifugation;
[0086] (4) The precipitate was resuspended in a protective solution to obtain a nanozyme immunoprobe.
[0087] The antibody dosage is 2.5-100 μg, preferably 10 μg; the blocking agent is selected from bovine serum albumin, casein, serum, or polyethylene glycol, preferably bovine serum albumin. The immune probe constructed using this method exhibits high antibody conjugation efficiency and good interfacial stability.
[0088] In some embodiments, based on the above-mentioned nanozyme immunoprobe, this application further provides a method for preparing an immunochromatographic test strip, comprising:
[0089] (1) Pre-treat the sample pad to improve sample wettability and reduce non-specific adsorption;
[0090] (2) Spray test lines and quality control lines onto the nitrocellulose membrane;
[0091] (3) Assemble the sample pad, nitrocellulose membrane and absorbent pad onto the carrier in sequence and cut them into test strips.
[0092] The immunochromatographic test strip of this application is based on the principle of competitive immunoassay and is used to detect small molecule substances with a relative molecular mass ≤1000, including at least one of pesticides, antibiotics, mycotoxins or illegal additives, and is preferably used for the detection of chloramphenicol.
[0093] During testing, the sample to be tested is mixed with the nanozyme immunoprobe and then added to the test strip. Qualitative analysis is achieved by observing changes in the detection line signal. At the same time, by adding a chromogenic substrate, the signal is amplified by the peroxidase-like catalytic effect of the nanozyme, achieving highly sensitive quantitative detection.
[0094] Compared with existing technologies, the gold-based nanozyme of this application has the following advantages:
[0095] By introducing Au into a multi-metal entropy nanozyme system, a functional interface with Au-S specific coordination ability is constructed on its surface, achieving efficient and stable antibody immobilization. Simultaneously, the mesoporous structure provides a high specific surface area and multi-site binding interface, enhancing antibody loading capacity. The synergistic effect of the multi-metal further optimizes the surface electronic structure, endowing the material with excellent peroxidase-like catalytic activity, enabling signal amplification. Thus, a unified integration of biorecognition and signal amplification is achieved, significantly improving detection sensitivity and stability, overcoming the shortcomings of insufficient catalytic performance of traditional gold nanoparticles and limited coupling ability of non-gold-based nanozymes.
[0096] The present application will be further described in detail below through specific embodiments. The following embodiments are only for further illustration of the present application and should not be construed as limiting the present application.
[0097] Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0098] Example
[0099] I. Preparation and Detection of Mesoporous Gold-Based Nanozymes
[0100] The precious metal salt precursor and ascorbic acid used in this example were purchased from Aladdin Biochemical Reagent Co., Ltd., the surfactant was purchased from Sigma-Aldrich Biochemical Reagent Co., Ltd., and the organic solvent and hydrochloric acid solution were purchased from Sinopharm Group Co., Ltd.
[0101] Weigh 10-100 mg of surfactant into a 20 mL glass reaction flask. The surfactant is selected from one or two of PEO-b-PMMA block copolymer, Pluronic F127, polyvinylpyrrolidone, or polyethylene glycol. Add 4 mL of solvent, which is N,N-dimethylformamide (DMF) or a mixture of DMF and deionized water. Sonicate the solution at room temperature for 5-15 min until it is completely dissolved, yielding a homogeneous and transparent solution.
[0102] Add 0.2-0.5 mL of 6.0 M hydrochloric acid solution to the above solution and mix well to adjust the acidity of the system and promote the formation of a stable self-assembled structure of the surfactant.
[0103] Subsequently, metal precursor solutions were added to the system in sequence, including: chloroauric acid solution (HAuCl4), potassium chloroplatinate solution (K2PtCl4), sodium rhodium chloride solution (Na3RhCl6), and copper chloride solution (CuCl2). The total volume of the metal salt solutions was 2 mL, and the total concentration was 40 mM. After mixing, the mixture was gently shaken to ensure uniform dispersion.
[0104] Add 2-5 mL of 100 mM L-ascorbic acid aqueous solution as a reducing agent to the above system, and gently shake for 0.5-3 min to ensure thorough mixing. Then transfer the reaction solution to a constant temperature water bath at 70-90℃ and allow it to stand for 8-24 h to achieve synergistic reduction of multi-metal precursors and formation of nanostructures.
[0105] After the reaction was completed, the product was separated by centrifugation at 10,000 rpm for 10 min. The precipitate was washed three times with a 1:1 volume ratio of ethanol / deionized water mixture to remove unreacted substances and impurities. Finally, it was dried under vacuum to obtain mesoporous gold-based nanozymes.
[0106] Figure 1 This paper illustrates the preparation process and formation mechanism of the mesoporous gold-based multi-principal-component nanozyme in this example. The method in this embodiment utilizes the amphiphilic self-assembly of surfactants to form a soft template, providing spatial confinement and structural guidance for the mesoporous structure. In an acidic environment, the coordination state and dispersion behavior of the multi-metal precursors are effectively regulated, resulting in a uniform distribution of Au, Pt, Rh, and Cu ions in the system and inhibiting metal phase separation. Under the action of L-ascorbic acid, multiple metal ions undergo synergistic reduction under mild conditions, gradually nucleating and growing under the synergistic regulation of the template confinement and the acidic environment, ultimately forming a multi-principal-component nanostructure with a uniform elemental distribution. Simultaneously, the template structure induces the formation of interconnected channels during the reaction, thereby constructing a mesoporous structure with a high specific surface area.
[0107] Building upon the methods described above, this example further optimizes the catalytic performance of gold-based nanozymes by adjusting the Au to Pt ratio, as detailed below:
[0108] Weigh out surfactant Pluronic F127 and add it to a 20 mL glass reaction flask. Add 4 mL of deionized water as a solvent and sonicate at room temperature for 10 min to fully dissolve it and form a homogeneous dispersion. Then add 0.4 mL of 6.0 M hydrochloric acid solution and mix thoroughly to regulate the acidic environment of the system and promote the uniform dispersion of the metal precursor.
[0109] Metal precursor solutions, including chloroauric acid solution (HAuCl4), potassium chloroplatinate solution (K2PtCl4), sodium rhodium chloride solution (Na3RhCl6), and copper chloride solution (CuCl2), were added sequentially to the above system, resulting in molar ratios of Au, Pt, Rh, and Cu of 2:1:1:1, 1:1:1:1, 1:2:1:1, or 1:3:1:1, respectively. After gentle shaking to ensure uniform dispersion of the metal ions, 4 mL of 100 mM L-ascorbic acid solution was added as a reducing agent, and shaking was continued for approximately 2 min. Subsequently, the reaction system was transferred to an 80°C constant temperature water bath and reacted for 12 h to achieve synergistic reduction of multiple metal ions and formation of nanostructures.
[0110] After the reaction was completed, the product was collected by centrifugation (10,000 rpm, 10 min) and washed three times with a 1:1 volume ratio of ethanol / deionized water mixture to remove unreacted substances and impurities. Finally, the product was obtained by vacuum drying.
[0111] The catalytic performance and morphology of AuPtRhCu nanozymes prepared under different Au / Pt ratios were compared, and the results are as follows: Figure 2 As shown.
[0112] Methods for evaluating the catalytic performance of AuPtRhCu nanozymes include:
[0113] (1) The nanozyme was added to the TMB and H2O2 system, and its catalytic color development ability was evaluated by measuring the change in absorbance at 652 nm;
[0114] (2) The specific activity of nanozymes per unit mass was calculated by monitoring the rate of change of absorbance in the initial stage of the reaction;
[0115] (3) By changing the substrate concentration, Michaelis-Menten kinetic curves were established, and Km and Vmax were calculated to evaluate the substrate affinity and catalytic efficiency of the nanozyme.
[0116] like Figure 2 As shown in Figures a and b, with the increase of the Pt ratio, the catalytic reaction rate and color intensity of the nanozyme in the TMB-H2O2 system are significantly enhanced, indicating that Pt mainly acts as the catalytic active center in the system, and its increased content is beneficial to increasing the number of surface active sites, thereby improving the peroxidase-like catalytic ability. Figure 2As shown in Figures c through f, the nanozymes obtained with different Au:Pt ratios did not exhibit significant changes in overall morphology, maintaining a stable mesoporous structure, indicating that component regulation does not disrupt the basic structural framework of the material. However, when the Au:Pt molar ratio was 1:2, the nanoparticle surface exhibited a more pronounced dendritic structure with more low-coordination atomic sites, which is beneficial for the catalytic reaction. Based on the comprehensive analysis of catalytic performance and structural characteristics, the nanozyme achieves a better balance between active site exposure and structural stability under the Au:Pt=1:2 condition. Therefore, the preferred molar ratio of Au, Pt, Rh, and Cu is 1:2:1:1.
[0117] It is understandable that the nanozymes obtained under different Au:Pt ratios did not show significant changes in overall morphology. Therefore, based on the above experiments, by appropriately adjusting the proportions of each component, for example, the molar ratio of Au, Pt, Rh, and Cu being (0.5-3):(1-3):(0.5-2):(0.5-2), mesoporous AuPtRhCu nanozymes similar to those in this example can also be prepared. The only difference is that the number of low-coordination atomic sites on the surface of the nanoparticles differs due to the different ratios, resulting in different degrees of improvement in peroxidase-like catalytic activity. In other words, different ratios of the metal precursors do not affect the structure of the AuPtRhCu nanozymes, but mainly affect the number of catalytically active sites on their surface and their catalytic activity.
[0118] Further characterization results of the AuPtRhCu nanozymes prepared under the above-mentioned preferred ratio conditions are as follows: Figure 3 As shown. Figure 3 As shown in Figure a, SEM reveals a distinct mesoporous structure; TEM ( Figure 3 Figure b) shows that the nanoparticles have a uniform dendritic structure with a particle size of approximately 60-70 nm; Energy Dispersive X-ray spectroscopy (EDS) and elemental distribution map (EDX) are also shown. Figure 3 Figures c and d show that the metal elements are uniformly distributed with no obvious phase separation. Furthermore, dynamic light scattering (DLS) testing results indicate an average hydrated particle size of 78.3 nm and a polydispersity index of 0.13, demonstrating good dispersibility and particle size uniformity. Figure 3 As shown in Figure e.
[0119] II. Comparison of the activities of different nanozymes
[0120] This example further tests the peroxidase-like catalytic performance of the AuPtRhCu nanozyme (molar ratio of Au, Pt, Rh, and Cu is 1:2:1:1) with the above-preferred formulation, and compares it with PdPtRhCu nanozyme and gold nanoparticles (AuNPs). The experiments included catalytic colorimetric verification, specific activity (SA) determination, and analysis of enzyme kinetic parameters (Km, Vmax), all performed in 96-well plates with a total volume of 200 μL per well.
[0121] The preparation method of PdPtRhCu nanozymes is similar to that of AuPtRhCu nanozymes, with only some appropriate adjustments. Specifically, it includes: firstly, adding 5 mg of PEO... 10500 -b-PMMA 18000 The solution was added to a 20 mL glass sample vial and completely dissolved in 0.8 mL of N,N-dimethylformamide (DMF). Subsequently, 0.2 mL of deionized water, 0.4 mL of 6 M hydrochloric acid (HCl), 0.8 mL of 40 mM potassium chloroplatinate (K₂PtCl₄) solution, 0.4 mL of 40 mM sodium chloropalladium (Na₂PdCl₄) solution, 0.4 mL of 40 mM sodium chlororhodium (Na₃RhCl₆) solution, 0.6 mL of 40 mM ruthenium chloride (RuCl₃·xH₂O) solution, and 2.0 mL of 0.1 mL L-ascorbic acid (L-AA) solution were added sequentially. The resulting mixture was reacted at 70 °C for 6 h to obtain PtPdRhRu multimetallic nanomaterials.
[0122] The synthesis method of AuNPs includes: The blue-capped flask used for AuNP synthesis was immersed in aqua regia (HCl:HNO3 = 3:1 (v:v)) for 30 min, then rinsed three times with ultrapure water, and finally completely dried in a 50℃ drying oven. 4, 6.5, 8, and 10 mL of trisodium citrate aqueous solution (38.8 mM) were rapidly added to 100 mL of boiling HAuCl4 aqueous solution (1 mM), respectively. Heating and stirring were continued for 15 min, during which the solution color gradually changed from yellow to deep blue, and finally to a stable wine red; the heating and stirring temperature was the boiling point of chloroauric acid, approximately 100℃. After the reaction was complete, the solution was cooled to room temperature and stored in a 4℃ refrigerator for later use.
[0123] (1) Verification of catalytic colorimetric ability
[0124] Dispersions of AuPtRhCu, PdPtRhCu, and AuNPs (0.1 mg / mL) were prepared separately. In each well of a 96-well plate, 140 μL of acetate-sodium acetate buffer (pH 4.0), 20 μL of TMB solution (10 mM) (final concentration 1.0 mM), 20 μL of H₂O₂ solution (1M) (final concentration 100 mM), and 20 μL of the nanomaterial dispersion (final concentration 10 μg / mL) were added. After mixing, the mixture was incubated at room temperature for 5–10 min, and the absorbance was measured at 652 nm. The system without nanomaterials served as a blank control.
[0125] (2) Specific activity (SA) determination
[0126] After adding the nanomaterials to the above reaction system, the mixture was immediately homogenized, and the absorbance change was continuously monitored at 652 nm (recorded every 10 s for 1 min). The absorbance change rate (ΔA / Δt) was calculated based on the initial linear phase. The calculation formula is as follows:
[0127] v = (ΔA / Δt×V) / ε×l
[0128] Where V is the total reaction volume (200 μL), and ε is the molar extinction coefficient of TMB oxide at 652 nm (3.9 × 10⁻⁶). 4 L·mol -1 ˙cm -1 ); l represents the effective optical path. The calculation formula is as follows:
[0129] SA=v / m
[0130] Where m is the mass of the nanozyme. 1 U is defined as the catalytic capacity to produce 1 μmol of oxidation product per minute.
[0131] (3) Determination of enzyme kinetic parameters
[0132] Using AuPtRhCu nanozymes as the research object, under the condition of a fixed final H₂O₂ concentration of 10 mM, the initial reaction rate v was measured at different substrate concentrations by varying the TMB concentration (0.025–1 mM). Km and Vmax were calculated using the Michaelis-Menten model and the Lineweaver-Burk double reciprocal equation. The formulas are as follows:
[0133] 1 / V=(Km / Vmax)˙(1[S]) + 1 / Vmax
[0134] Wherein, Km is used to reflect the apparent affinity of AuPtRhCu nanozymes for the substrate, and Vmax is used to reflect their maximum catalytic rate.
[0135] like Figure 4 As shown in Figure a, no obvious color development was observed in the TMB-only or TMB+H2O2 systems, but blue oxidation products were produced after the addition of nanomaterials, indicating that all three materials possess peroxidase-like activity. Among them, the AuPtRhCu nanozyme exhibited the most significant color development, with an absorbance of 1.56 at 652 nm, significantly higher than PdPtRhCu (1.23) and AuNPs (0.12), indicating its stronger catalytic ability. Figure 4As shown in Figure b, the specific activity of the AuPtRhCu nanozyme is 273 U / mg, which is significantly higher than that of AuNPs (2.79 U / mg), representing an improvement of nearly two orders of magnitude. Simultaneously, it is at a comparable or slightly better level than the PdPtRhCu nanozyme, indicating that the introduction of Au to construct the bioconjugation interface did not reduce its catalytic performance. Enzyme kinetic analysis results show that the Km of the AuPtRhCu nanozyme is 0.151 mM, and the Vmax is 2.65 × 10⁻⁶. -7 The M / s ratio indicates that it has a high apparent affinity for the substrate and a fast catalytic reaction rate. These results demonstrate that the AuPtRhCu nanozyme maintains or outperforms the catalytic performance of traditional PdPtRhCu nanozymes while exhibiting significantly higher catalytic activity compared to AuNPs, along with good substrate affinity, providing an important foundation for its signal amplification application in subsequent immunoassays.
[0136] III. Comparative Evaluation of the Conjugation Efficiency of Different Nanoparticles with Antibodies
[0137] This example further evaluates the performance of the AuPtRhCu nanozyme with the above-preferred formulation in protein coupling, and compares it with PdPtRhCu nanozyme and AuNPs to verify its advantages in antibody immobilization efficiency and interfacial stability. The PdPtRhCu nanozyme and AuNPs used for comparison are the same as in "II. Comparison of the Activities of Different Nanozymes".
[0138] (1) Nanozyme-antibody conjugation
[0139] Antibody conjugation experiments were conducted using AuPtRhCu nanozyme, PdPtRhCu nanozyme, and AuNPs dispersions, respectively. The specific steps are as follows: 100 μL of nanoparticle dispersion was added to a centrifuge tube, followed by 900 μL of deionized water. The pH of the system was adjusted to 7.5-9.0 using 0.1 mol / L potassium carbonate solution; in this example, the pH was adjusted to 8.3. Then, 2.5-100 μg of antibody solution was added. In this example, antibody dosages of 2.5 μg, 10 μg, 25 μg, 50 μg, and 100 μg were tested. The mixture was incubated at room temperature for 10-60 min. Specifically, the incubation time for AuNPs particles was 60 min, and the incubation times for AuPtRhCu and PdPtRhCu were 10 min and 30 min, respectively, to ensure sufficient binding of antibody molecules to the nanoparticle surface.
[0140] (2) Blocking and purification
[0141] After incubation, 100 μL of 10% bovine serum albumin (BSA) solution was added for blocking, and incubation continued for 10–60 min to reduce nonspecific adsorption. The mixture was then centrifuged at 10,000 rpm for 10 min, and the supernatant was collected for antibody quantification. The precipitate was resuspended in a reconstitution solution containing 2.5% BSA and 5% sucrose and stored at 4°C to obtain the nanoparticle immunoprobe.
[0142] (3) Antibody conjugation efficiency determination
[0143] The content of unbound antibodies in the supernatant was determined using a protein quantification method, and the coupling efficiency was calculated using the following formula:
[0144] Conjugation efficiency = (1 - amount of antibody in supernatant / total amount of antibody) × 100%
[0145] Each experiment had 3 parallel samples, and the average value was used for comparison and analysis.
[0146] like Figure 5 As shown in Figures a to c, within the antibody addition range of 2.5–100 μg, the coupling efficiency of AuPtRhCu nanozymes was 76.8–97.7%, significantly higher than that of PdPtRhCu nanozymes (37.7–85.7%) and AuNPs (32.4–87.9%). With increasing antibody addition, the coupling efficiency of PdPtRhCu and AuNPs systems decreased significantly, while AuPtRhCu maintained a higher level, indicating that it has higher antibody loading capacity and better interfacial stability.
[0147] like Figure 6 As shown, the binding mechanisms of the three materials with antibodies differ significantly. PdPtRhCu nanozymes primarily rely on electrostatic interactions, hydrophobic interactions, and weak coordination to achieve non-specific adsorption. While AuNPs can bind antibodies via Au-S interactions, their dense structure limits the number of binding sites. In contrast, the exposed Au sites on the surface of AuPtRhCu nanozymes can form stable Au-S coordination bonds with the thiol groups in antibodies. Simultaneously, its mesoporous / dendritic structure provides a multi-site binding interface, and the multi-metal components further regulate the surface electronic structure and enhance interfacial stability. The combined effect of "Au-S specific binding, multi-site adsorption, and multi-metal synergistic effect" makes AuPtRhCu nanozymes significantly superior to the control material in terms of antibody conjugation efficiency and stability.
[0148] IV. Preparation method and application of immunochromatographic test strips based on AuPtRhCu nanozyme probes
[0149] This embodiment illustrates the construction method of the AuPtRhCu nanozyme immunoprobe with the above-preferred formulation in an immunochromatographic test strip and its application in small molecule detection.
[0150] 1. Preparation method of immunochromatographic test strips
[0151] (1) Sample pad treatment
[0152] A glass fiber membrane (1×30 cm) was used as the sample pad and immersed in borate buffer (BBS, pH 7.4) containing 1% bovine serum albumin (BSA), 1% polyethylene glycol 4000 (PEG4000), 0.1% polyvinylpyrrolidone (PVP40000), and 0.01-5% Tween-20. After treatment, the membrane was dried at 45°C for 2 h for later use. This step was used to improve sample wettability and reduce non-specific adsorption.
[0153] (2) Preparation of nitrocellulose membrane
[0154] Chloramphenicol complete antigen (CAP-BSA) and goat anti-mouse IgG antibody were diluted separately using 0.01 M phosphate-buffered saline (PBS, pH 7.4). They were then sprayed onto nitrocellulose membranes at a rate of 0.75 μL / cm using a spray membrane applicator to form a detection line (T line) and a control line (C line). The T line was used to immobilize the complete antigen, and the C line was used to capture unbound probes. After spraying, the membranes were dried at 45°C for 2 h for later use.
[0155] (3) Assembly of test strips
[0156] The sample pad, nitrocellulose membrane, and absorbent pad are sequentially adhered to a PVC base plate, with each part overlapping by approximately 2 mm. After assembly, the strips are cut into 3.5 mm wide test strips and sealed for storage. The structure of the test strip in this example is as follows. Figure 7 As shown.
[0157] 2. How to use the test strips
[0158] Take 100 μL of pretreated sample (e.g., chicken extract) and add it to a reaction system containing 2.5 μL of AuPtRhCu nanozyme immunoprobe. After incubating at room temperature for 3 min, drop the solution onto the sample pad of the test strip. Perform a chromatographic reaction driven by capillary action. Observe the color development of the T and C lines after about 10 min to achieve rapid qualitative detection. Further, add a chromogenic substrate (e.g., TMB or AEC) to the detection line region. Utilize the nanozyme catalytic reaction to amplify the signal and achieve highly sensitive quantitative analysis.
[0159] The preparation method of chicken extract includes: weighing 1 g of homogenized chicken sample, adding 2 mL of ethyl acetate, vortexing thoroughly to extract; collecting the extract after centrifugation, and evaporating and concentrating to dryness; then adding 1 mL of PBS buffer to redissolve the residue to obtain the sample extract for subsequent detection.
[0160] 3. Detection Principle
[0161] This example immunochromatographic test strip is constructed based on the principle of competitive immunoassay, and its detection mechanism is as follows: Figure 8 As shown, the target small molecules (such as chloramphenicol) in the sample competitively bind to the nanozyme-labeled antibody: when the concentration of the target in the sample is high, the antibody preferentially binds to the free antigen, thereby reducing its capture amount on the detection line and resulting in a weakened detection line signal; when the concentration of the target is low, more probes are captured on the detection line, generating a stronger signal. The AuPtRhCu nanozyme probe serves as both a signal labeling and catalytic amplification unit, catalyzing the generation of a chromogenic product under the action of an external substrate, achieving secondary amplification of the detection signal, thereby significantly improving detection sensitivity.
[0162] Compared with traditional AuNPs labeling systems, the nanozyme probe in this example has the following advantages: efficient and stable antibody conjugation is achieved through Au-S bonds; the mesoporous structure provides a high specific surface area and multi-site binding interface, improving antibody loading capacity; and the synergistic effect of multiple metals endows it with excellent peroxidase-like activity, realizing signal amplification. Thus, it achieves an integrated "biorecognition-signal amplification" system, significantly improving the sensitivity and stability of immunochromatographic detection.
[0163] The above description, in conjunction with specific embodiments, provides a further detailed explanation of this application and should not be construed as limiting the specific implementation of this application to these descriptions. Those skilled in the art to which this application pertains can make several simple deductions or substitutions without departing from the concept of this application.
Claims
1. A gold-based nanozyme, characterized in that: The gold-based nanozyme contains Au, Pt, Rh, and Cu elements, and has a multi-principal nanostructure and mesoporous structure in which Au, Pt, Rh, and Cu are uniformly distributed at the atomic and / or nanoscale. The Au element is at least partially exposed on the surface of the gold-based nanozyme. The molar ratio of Au, Pt, Rh, and Cu in the gold-based nanozyme is (0.5-3):(1-3):(0.5-2):(0.5-2). The preparation method of the gold-based nanozyme includes the following steps: (1) A surfactant is added to a solvent to form a uniform dispersion system, wherein the surfactant can form a micelle structure in the solvent; (2) Add an acidic solution to the homogeneous dispersion system to adjust the reaction environment to a strongly acidic environment; (3) Add metal precursor solutions of Au, Pt, Rh and Cu in sequence; (4) Add a mild reducing agent and react at 70-90℃ for 8-24 h; (5) Centrifuge, wash and dry to obtain the gold-based nanozyme; Wherein, the surfactant is Pluronic F127, the acidic solution is a hydrochloric acid solution with a concentration of 4-8 mol / L, the pH of the strongly acidic environment is 0.5-1.5, and the mild reducing agent is L-ascorbic acid.
2. The gold-based nanozyme according to claim 1, characterized in that: The gold-based nanozyme has a dendritic structure.
3. The method for preparing the gold-based nanozyme according to claim 1 or 2, characterized in that: Includes the following steps, (1) A surfactant is added to a solvent to form a uniform dispersion system, wherein the surfactant can form a micelle structure in the solvent; (2) Add an acidic solution to the homogeneous dispersion system to adjust the reaction environment to a strongly acidic environment; (3) Add metal precursor solutions of Au, Pt, Rh and Cu in sequence; (4) Add a mild reducing agent and react at 70-90℃ for 8-24 h; (5) Centrifuge, wash and dry to obtain the gold-based nanozyme; Wherein, the surfactant is Pluronic F127, the acidic solution is a hydrochloric acid solution with a concentration of 4-8 mol / L, the pH of the strongly acidic environment is 0.5-1.5, and the mild reducing agent is L-ascorbic acid.
4. The preparation method according to claim 3, characterized in that: The solvent is water or a mixture of water and an organic solvent.
5. The preparation method according to claim 4, characterized in that: The concentration of the surfactant in the solvent is 1.25-10 mg / mL.
6. The preparation method according to claim 3, characterized in that: Step (1) uses ultrasonic dispersion of surfactant to form a uniform dispersion system.
7. The preparation method according to claim 3, characterized in that: In step (3), the metal precursor solution of Au is at least one of chloroauric acid, sodium tetrachloroaurate, and potassium tetrachloroaurate.
8. The preparation method according to claim 3, characterized in that: The metal precursor solution for Pt is at least one of potassium chloroplatinate, chloroplatinic acid, sodium hexachloroplatinate, potassium hexachloroplatinate, and ammonium hexachloroplatinate.
9. The preparation method according to claim 3, characterized in that: The metal precursor solution of Rh is at least one of sodium rhodium chloride, rhodium chloride, potassium rhodium chloride, rhodium chloride, and hydrated rhodium chloride.
10. The preparation method according to claim 3, characterized in that: The metal precursor solution of Cu is at least one of copper chloride, copper nitrate, copper sulfate, and copper acetate.
11. The use of the gold-based nanozyme according to claim 1 or 2 in the preparation of protein-coupled reagents, nanozyme immunoprobes, or immunochromatographic test strips.
12. A protein coupling method, characterized in that: Includes the following steps, (1) Disperse the gold-based nanozyme according to claim 1 or 2 in an aqueous solution; (2) Adjust the pH of the system to 7.5-9.0; (3) Add antibody and incubate to fix the antibody on the surface of the gold-based nanozyme through Au-S coordination; (4) Add a blocking agent to reduce non-specific adsorption; (5) Centrifuge and resuspend to obtain nanozyme immunoprobes for protein coupling.
13. The protein coupling method according to claim 12, characterized in that: The blocking agent is at least one of bovine serum albumin, casein, and polyethylene glycol.
14. A nanozyme immunoprobe, characterized in that: It is formed by conjugation of the gold-based nanozyme as described in claim 1 or 2 with an antibody.
15. An immunochromatographic test strip, characterized in that: It includes a sample pad, a nitrocellulose membrane, and an absorbent pad, wherein the nitrocellulose membrane is provided with test lines and control lines, wherein the test lines or control lines contain the nanozyme immunoprobe as described in claim 14.
16. A reagent kit for immunoassay, characterized in that: Contains the gold-based nanozyme of claim 1 or 2, the nanozyme immunoprobe of claim 14, or the immunochromatographic test strip of claim 15.
Citation Information
Patent Citations
Signal-enhanced immunochromatography test paper as well as detection method and application thereof
CN118858618A